Gellan gum hydrogels with enzyme-sensitive biodegradation and endothelial cell biorecognition sites - Silva, Lucília Pereira (2018)
The survival of a biomaterial or tissue engineered construct is mainly hampered by the deficient microcirculation in its core, and limited nutrients and oxygen availability to the implanted or colonizing host cells. Aiming to address these issues, we herein propose bioresponsive gellan gum (GG) hydrogels that are biodegradable by metalloproteinase 1 (MMP-1) and enable endothelial cells adhesion and proliferation. GG is chemically functionalized with divinyl sulfone (DVS) and then biofunctionalized with thiol cell-adhesive peptides (T1 or C16) to confer GG endothelial cell biorecognition cues. Biodegradable hydrogels are then formed by Michael type addition of GGDVS or/and peptide-functionalized GGDVS with a dithiol peptide crosslinker sensitive to MMP-1. The mechanical properties (6 to 5580 Pa), swelling (17 to 11), MMP-1-driven degradation (up to 70%), and molecules diffusion coefficients of hydrogels are tuned by increasing the polymer amount and crosslinking density. Human umbilical cord vein endothelial cells depict a polarized elongated morphology when encapsulated within T1-containing hydrogels, in contrast to the round morphology observed in C16-containing hydrogels. Cell organization is favored as early as 1 d of cell culture within the T1-modified hydrogels with higher concentration of peptide, while cell proliferation is higher in T1-modified hydrogels with higher modulus. In conclusion, biodegradable and bioresponsive GGDVS hydrogels are promising endothelial cell responsive materials that can be used for vascularization strategies.